Kinetic study of methanol dehydration to DME on Zr-loaded P-containing mesoporous activated carbon catalyst. - Palomo-Jiménez, José; Rodríguez-Cano, Miguel Ángel; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (My University, 2019)
The selective methanol dehydration to DME using a Zr-loaded P-containing activated carbon catalyst have been studied. The activated carbon was prepared by chemical activation of olive stones with phosphoric acid. Then, the resulting activated carbon was loaded with a 5 % of Zr by incipient wetness impregnation. A kinetic study for the selective methanol dehydration to DME was carried out and the corresponding kinetic and thermodynamic parameters were calculated. Three reaction mechanism were proposed. A Langmuir-Hinshelwood like mechanism was the one that better reproduced the experimental data.
Keywords: Metanol; Carbón activado; Dimetil-eter (DME); Mesoporous carbon; Heterogeneous catalysis; Methanol dehydration; dimethyl ether; Phosphorus functionalization; Zirconium